2015
DOI: 10.1111/cid.12386
|View full text |Cite
|
Sign up to set email alerts
|

A 15‐Year Comparative Prospective Study of Surgical and Prosthetic Care and Aftercare of Overdenture Treatment in the Atrophied Mandible: Augmentation Versus Nonaugmentation

Abstract: The only difference in the need for surgical and prosthetic (after) care was the extra time needed for performing augmentation surgery and the higher risk on implant loss in augmented mandibles. Otherwise, the need for care and aftercare was of the same magnitude. Thus, when applicable, nonaugmentation surgery is preferred as no general anesthesia is needed and the morbidity is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 27 publications
1
25
0
1
Order By: Relevance
“…As can be seen in the data presented in Table , a clear trend was the evaluation of implant survival solely, rather than overall success, when defining the success criteria. Thus, 12 studies cited implant survival as their main outcome, while five studies stated that they intended to use some predefined criteria for success assessment (eg, Albrektsson et al, Buser et al), although this goal was not necessarily achieved. Of those studies reporting a success rate, one study reported a survival rate and patients' subjective sensation, one study reported a survival rate, clinical parameters and patients' subjective sensation, and one study reported a survival rate and clinical parameters .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As can be seen in the data presented in Table , a clear trend was the evaluation of implant survival solely, rather than overall success, when defining the success criteria. Thus, 12 studies cited implant survival as their main outcome, while five studies stated that they intended to use some predefined criteria for success assessment (eg, Albrektsson et al, Buser et al), although this goal was not necessarily achieved. Of those studies reporting a success rate, one study reported a survival rate and patients' subjective sensation, one study reported a survival rate, clinical parameters and patients' subjective sensation, and one study reported a survival rate and clinical parameters .…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies reported the full extent (ie, on the additional three parameters in the success criteria by Albrektsson and colleagues) of the aspects . Four studies reported solely on survival without reporting any of the additional parameters for success . The three remaining aspects, which should be assessed along with survival according to Albrektsson et al, were reported in a broad palette of combinations by the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…38,39 This also included mucositis and adjustments of prostheses. Prosthetic care and aftercare was not taken into account for reason that in previous studies from our research group (long-term) care and aftercare was described in detail.…”
Section: Patient-reported Outcomesmentioning
confidence: 99%